2011
DOI: 10.1210/en.2011-0286
|View full text |Cite
|
Sign up to set email alerts
|

Physiological and Pharmacological Mechanisms through which the DPP-4 Inhibitor Sitagliptin Regulates Glycemia in Mice

Abstract: Inhibition of dipeptidyl peptidase-4 (DPP-4) activity improves glucose homeostasis through a mode of action related to the stabilization of the active forms of DPP-4-sensitive hormones such as the incretins that enhance glucose-induced insulin secretion. However, the DPP-4 enzyme is highly expressed on the surface of intestinal epithelial cells; hence, the role of intestinal vs. systemic DPP-4 remains unclear. To analyze mechanisms through which the DPP-4 inhibitor sitagliptin regulates glycemia in mice, we ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
134
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 140 publications
(144 citation statements)
references
References 55 publications
9
134
0
1
Order By: Relevance
“…Thus it has been demonstrated in subjects with type 2 diabetes both for sitagliptin (14) and vildagliptin (49) that insulin secretion also after intravenous glucose administration is stimulated during DPP-4 inhibition with no or only minimal increase in circulating GLP-1 levels, which would suggest contribution by autonomic nerves and/or other bioactive peptides. A finding by Salehi et al that GLP-1 receptor antagonism reduces the insulin response to intravenous glucose in humans may support the neural hypothesis (50).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus it has been demonstrated in subjects with type 2 diabetes both for sitagliptin (14) and vildagliptin (49) that insulin secretion also after intravenous glucose administration is stimulated during DPP-4 inhibition with no or only minimal increase in circulating GLP-1 levels, which would suggest contribution by autonomic nerves and/or other bioactive peptides. A finding by Salehi et al that GLP-1 receptor antagonism reduces the insulin response to intravenous glucose in humans may support the neural hypothesis (50).…”
Section: Discussionmentioning
confidence: 99%
“…They demonstrated that administration of low oral doses of sitagliptin (40-120 mg) improved glucose tolerance and increased circulating insulin without affecting DPP-4 activity in peripheral plasma. It should be emphasized that even though DPP-4 activity was not altered in peripheral plasma, the glucose-lowering effect of sitagliptin was still GLP-1 dependent since the effect was lost in mice with genetic deletion of GLP-1 receptors (14). While not inhibiting DPP-4 activity in peripheral plasma, these low doses of sitagliptin inhibited DPP-4 activity locally in the duodenum, jejunum, and ileum.…”
Section: Dpp-4 Inhibition In the Gutmentioning
confidence: 96%
See 1 more Smart Citation
“…For example, oral administration of low doses of DPP-4 inhibitor, sitagliptin, aimed at selectively inhibiting intestinal, but not systemic, DPP-4 activity still resulted in enhanced glycemic control and plasma insulin levels through activation of local GLP-1R on the vagus nerve. This indicates a predominant role for enhancement of the GLP-1 gut-brain-periphery axis in the ability of sitagliptin to reduce local intestinal DPP4 activity and regulate glycemia (43). Furthermore, the rapid remission of type 2 diabetes following gastric bypass surgeries has been hypothesized to be mediated by GLP-1 (44,45).…”
Section: Glp-1 Action In the Gutmentioning
confidence: 99%
“…Thus, oral administration of a low dose of DPP-4 inhibitor to mice reduced glucose without inhibiting the circulating DPP-4 activity [7,8]. This would suggest that local DPP-4 activity is also important for the glucose-lowering action of DPP-4 inhibitors.…”
Section: Introductionmentioning
confidence: 99%